Catalytic Wet Air Oxidation of Phenol in a Trickle Bed Reactor - T. Mohammed, Wadood; M. Abdullah, Sama; M. Ghalib, Atheer (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Catalytic wet air oxidation of aqueous phenol solution was studied in a pilot plant trickle bed reactor using copper oxide catalyst supported on alumina and silica. Catalysts were prepared by impregnating method. Effect of feed solution pH (5.9, 7.3, and 9.2), gas flow rate (20%, 50%, 80%, and 100%), WHSV (1, 2, and 3 h-1), temperature (120°C, 140°C, and 160°C), oxygen partial pressure (6, 9, 12 bar), and initial phenol concentration (1, 2, and 4 g/l).Generally, the performance of the catalysts was better when the pH of feed solution was increased. The catalysts deactivation is related to the dissolution of the metal oxides from the catalyst surface due to the acidic conditions. Phenol oxidation reaction was strongly affected by WHSV, temperature, oxygen partial pressure, and initial phenol concentration. While gas flow rate had a marginal effect.